2018
DOI: 10.21608/edj.2018.77361
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Reproducibility of 3D Printed Dies versus Stone Dies

Abstract: Statement of the problem: researches studying the accuracy of the 3D printed dies were very rare. Aim:The aim of the current study was to assess the difference in accuracy and reproducibility of the three dimensionally printed dies versus the stone dies. Materials& Methods:A maxillary typodont (D13PP-TR.1; Nissan, Kyoto, Japan) model with missing upper 1st molar was prepared as master model. Two types of dies were obtained from the master model (n=6). Group 1 was the conventional stone dies using type IV stone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…9 However, physical casts with removable dies are still required, particularly when managing complex treatment plans or to improve esthetics. [8][9][10][11] A digital dental cast can be converted into a physical cast by using either subtractive or additive manufacturing. 12,13 Additive manufacturing has the advantage of fabricating complex structures with less waste material.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…9 However, physical casts with removable dies are still required, particularly when managing complex treatment plans or to improve esthetics. [8][9][10][11] A digital dental cast can be converted into a physical cast by using either subtractive or additive manufacturing. 12,13 Additive manufacturing has the advantage of fabricating complex structures with less waste material.…”
mentioning
confidence: 99%
“…16 Regardless of the manufacturing technique, accurate dental casts are essential to ensure precise prostheses. 1,12 Even though studies have shown that additively manufactured dental casts have an accuracy similar to that of gypsum casts, 4,5,10,[17][18][19][20] conflicting results have been reported. 4 Therefore, knowledge of the factors that affect the accuracy of additively manufactured casts, 21 including layer thickness, is essential.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…e outro não encontrou diferença com modelos DLP(MAHROUS;ABOULMAGD, 2018). Ainda, outro estudo não encontrou diferença na exatidão de modelos Hoffman; Cho e Bansal 2017 compararam as distâncias interproximais de modelos de gesso e SLA não seccionados e troquelizados obtidos a partir de manequim odontológico contendo preparo para PPF de três elementos e coroa unitária.…”
unclassified